The Influence of ACFTA on Indonesia’s Coal Exports to China from 2000-2022 - Malikah, Siti; Burhanudin, Ahmad Hammam; Sulistiyowati, Maya Indah; Hidayat, Manarul; Azzahra, Shona Eliza (Economics and Business International Conference Proceeding, 2024)
Southeast Asia (ASEAN) and China formed the ASEAN-China Free Trade Area (ACFTA) agreement to realize free trade in the Southeast Asia region and China. ACFTA is an agreement that has been agreed by ASEAN member countries with China in an effort to create an international free trade area by minimizing barriers that could hinder tariff or non-tariff trade, increasing market access, regulations and investment agreements. This research aims to determine whether ACFTA has had an impact on increasing the performance of Indonesian coal exports to China before and after the establishment of ACFTA. This research uses secondary data sources from 2000-2021 which originate from the agency center Indonesian statistics. Purposive sampling was used in this research and the sample selected was based on certain criteria that describe the trade balance. Average volume of coal exports to China per year is 623,0273 with a median of 600,8000. The results show that the ASEAN-China Free Trade Area (ACFTA) has a positive impact on Indonesian coal exports to China.